Stable vector bundles on curves: numerical invariants of their extremal subbundles - Ballico, E. (MATHEMATICA SCANDINAVICA, 2001)
Let X be a smooth projective curve of genus g ≥ 2 and E a rank r vector bundle on X. If 1 ≤ t < r set s_t(E):= sup t(deg(E)) - r(deg(F)), where F is a rank t subsheaf of E brace . Here we construct rank r stable vector bundles E on X such that the sequence s_t(E) brace _1 ≤ t<r has a prescribed value and the set of all subsheaves of E with maximal degree may be explicitely described.